The oral health impact profile and well-being on mothers and preschool children - Silva, Bianca Núbia Souza [UNESP]; de Campos, Lucas Arrais [UNESP]; Maroco, João; Campos, Juliana Alvares Duarte Bonini [UNESP] (Springer Nature, 2024)
Objectives: to verify the contribution of mothers’ oral health impact profile to their children’s oral health profile and the contribution of mothers’ well-being and the caries index (dmft) to children’s well-being. Methods: This is a cross-sectional observational study. Mothers and pre-school children enrolled in public schools in the municipality of Araraquara-SP took part. The Oral Health Impact Profile Questionnaire (OHIP-14), Satisfaction with Life Scale (SWLS), Early Childhood Oral Health Impact Scale (ECOHIS) and the Autoquestionnaire Qualité de Vie Enfant Imagé (AUQEI) were used. To diagnose caries, a clinical examination was carried out to calculate the dmft index. Path analysis was carried out and the path coefficients were estimated (β) and evaluated using the z-test (α = 5%). Results: 443 children took part (5.19 ± 0.64 years; 52.4% boys) with an mean dmft of 1.31 ± 2.19. The mean age of the mothers was 33.4 ± 7.01 years. There was a significant impact of dmft and maternal well-being on the child’s subjective well-being (s2explained = 43%). The mothers’ oral health impact profile and the child’s caries experience had a significant influence on both the child (OHIP: β = 0.22; p < 0.001; dmft: β = 0.48; p < 0.001) and the family (OHIP: β = 0.29; p < 0.001; dmft: β = 0.32; p < 0.001). The child’s dmft (β=-0.10; p = 0.005) and the mothers’ subjective well-being (β=-0.61; p < 0.001) had a significant impact on the child’s subjective well-being. Conclusion: The mothers’ oral health impact profile and the child’s caries experience had an impact on both the child and the family. Mothers’ subjective well-being and caries experience should be considered when assessing the subjective well-being of Brazilian preschool children.
Keywords: Disease impact profile; Oral health; Parent-child; Well-being